Hubungan Kepemimpinan dan Motivasi Kerja Dengan Kinerja Guru di Madrasah Ibtidaiyah Kecamatan Losari Kabupaten Cirebon - Agus Karjuni; Dianah Dianah; Wawan Sonjaya; Junaedi Junaedi (Universitas Islam Bunga Bangsa Cirebon, 2020)
This research is motivated by data from RA / MI / DIN supervisors in Losari Subdistrict, Cirebon Regency in 2017. These data show contradictions where the qualifications of MI heads are very good while the teacher's performance is fairly good. The purpose of this study was to analyze data on: 1) a significant positive relationship between leadership and teacher work motivation; 2) a significant positive relationship between leadership and teacher performance; and 3) a significant positive relationship between teacher work motivation and teacher performance. The type of research used in this research is quantitative research with this type of research is correlational. The research was conducted at MI in the Losari District of Cirebon Regency. The population in this study were all MI teachers in Losari District, Cirebon Regency, West Java Province, totaling 50 teachers spread across 5 (five) Madrasah Ibtidaiyah (MI). The technique or method of collecting data in this study is a questionnaire. The analysis technique that the writer uses is the calculation with simple correlation analysis techniques. The results: 1) There is a significant positive relationship between leadership variables and teacher work motivation with a significance value of 0.000 Ë‚ 0.05, and a correlation level of 0.861; 2) There is a positive and significant relationship between leadership variables and teacher performance with a significance value of 0.000 Ë‚ 0.05, and a correlation level of 0.634; and 3) There is a positive and significant relationship between teacher work motivation variables and teacher performance with a significance value of 0.000 Ë‚ 0.05, and a correlation level of 0.539. Abstrak Penelitian ini dilatarbelakangi oleh data pengawas RA/MI/DIN di Kecamatan Losari Kabupaten Cirebon tahun 2017. Data tersebut menunjukkan hal yang kontradiktif dimana kualifikasi kepala MI berpredikat sangat baik sedangkan kinerja guru berpredikat cukup. Tujuan penelitian ini untuk menganalisis data tentang: 1) Hubungan positif yang signifikan antara kepemimpinan dengan motivasi kerja guru; 2) Hubungan positif yang signifikan antara kepemimpinan dengan kinerja guru; dan 3) Hubungan positif yang signifikan antara motivasi kerja guru dengan kinerja guru. Adapun jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dengan jenis penelitian adalah korelasional. Penelitian dilakukan pada MI di wilayah Kecamatan Losari Kabupaten Cirebon. Populasi dalam penelitian ini adalah seluruh guru MI di Kecamatan Losari Kabupaten Cirebon Provinsi Jawa Barat yang berjumlah 50 orang guru yang tersebar di 5 (lima) Madrasah Ibtidaiyah (MI). Tehnik atau cara pengumpulan data pada penelitian ini adalah angket. Teknik analisis yang penulis gunakan adalah perhitungan dengan teknik analisis korelasi sederhana. Hasil penelitian: 1) Adanya hubungan positif yang signifikan antara variabel kepemimpinan dengan motivasi kerja guru dengan nilai signifikansi 0,000 Ë‚ 0,05, dan tingkat korelsai sebesar 0,861; 2) Adanya hubungan positif dan signifikan antara variabel kepemimpinan dengan kinerja guru dengan nilai signifikansi 0,000 Ë‚ 0,05, dan tingkat korelsai sebesar 0,634; dan 3) Adanya hubungan positif dan signifikan antara variabel motivasi kerja guru dengan kinerja guru dengan nilai signifikansi 0,000 Ë‚ 0,05, dan tingkat korelasi sebesar 0,539.